2023
DOI: 10.3390/biology12060781
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Comprehensive Panel of Cultivated and Wild Vigna Species for Resistance to Pulse Beetle, Callosobruchus chinensis L.

Abstract: Pulses are a key source of dietary proteins in human nutrition. Despite several efforts to increase the production, various constraints, such as biotic and abiotic factors, threaten pulse production by various means. Bruchids (Callosobruchus spp.) are the serious issue of concern, particularly in storage conditions. Understanding host–plant resistance at morphological, biochemical and molecular levels is the best way to minimize yield losses. The 117 mungbean (Vigna radiata L. Wilczek) genotypes, including end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Kumari et al [54] explored the endemic wild Vigna species and identified some of the potential sources of resistance to yellow mosaic disease. Sahu et al [55] screened the cultivated wild Vigna gene pool and identified potential sources of bruchid resistance. Purwar et al [56] performed the expression of R genes in two wild Vigna species, and their comparative study with mungbean, and found the higher expression in wild species.…”
Section: Discussionmentioning
confidence: 99%
“…Kumari et al [54] explored the endemic wild Vigna species and identified some of the potential sources of resistance to yellow mosaic disease. Sahu et al [55] screened the cultivated wild Vigna gene pool and identified potential sources of bruchid resistance. Purwar et al [56] performed the expression of R genes in two wild Vigna species, and their comparative study with mungbean, and found the higher expression in wild species.…”
Section: Discussionmentioning
confidence: 99%